A Wireless ExG Interface for Patch-Type ECG Holter and EMG-Controlled Robot Hand - Kwangmuk Lee; Yun Young Choi; Dae Jung Kim; Hee Young Chae; Kyeonghwan Park; Young Min Oh; Sung Hun Woo; Jae Joon Kim (Sensors, 2017)
This paper presents a wearable electrophysiological interface with enhanced immunity to motion artifacts. Anti-artifact schemes, including a patch-type modular structure and real-time automatic level adjustment, are proposed and verified in two wireless system prototypes of a patch-type electrocardiogram (ECG) module and an electromyogram (EMG)-based robot-hand controller. Their common ExG readout integrated circuit (ROIC), which is reconfigurable for multiple physiological interfaces, is designed and fabricated in a 0.18 μm CMOS process. Moreover, analog pre-processing structures based on envelope detection are integrated with one another to mitigate signal processing burdens in the digital domain effectively.